The safety of Osmanthus fragrans ethanol extract treatment in BALB/c mice - Hung, Chien-Ya; Lin, Chih-Hung; Li, Kuo-Yu; Hung, Tsung-Jen; Huang, Fu-Long (International Journal of Pharmacology and Toxicology, 2013)
Background: Osmanthus fragrans flower, recently certificated as a new natural antioxidant, has been used in various foods. We performed an acute and subacute toxicological test for evaluating the safety and toxicity of 75 % ethanol extraction of Osmanthus fragrans (OFEE). Method: In the acute toxicity study, a single dose of 5 g/kg and 10 g/kg of the extract was administered orally to six mice. General behaviour, mortality and toxic symptoms were determined daily for 14 days. For the subacute toxicity, two groups of 12 mice received 0.9% normal saline (control) and 1 g/kg of the extract daily for 28 consecutive days by oral gavage. The animals were observed daily for abnormal clinical signs and death. Body weight, haematological and biochemical parameters of blood as well as kidney, liver, lung and spleen tissues histology were evaluated. Results: The total phenolic contents in OFEE were 371.71 ± 12.35 mg GAE/g extracts and total flavonoid contents were 47.23 ± 5.36 mg QE/g extract. OFEE did not cause any mortality or morbidity. Maximum tolerated dose (MTD) was 10 g/kg body weight in our BALB/c mice, which can be regarded as virtually non-toxic. Administration of OFEE at dose 1 g/kg/day for 28-day did not cause changed in hematological, biochemical assay, and histopathological conditions change, suggesting a no-observed-adverse-effect level (NOVEL) of 1 g/kg/day. Conclusion: We found no evidence of adverse effects in our laboratory test and pathological studies. 75 % ethanol extraction may safely be used in the research of Osmanthus fragrans in animal and probably human studies.